PENGAWASAN DINAS PERHUBUNGAN KOMUNIKASI INFORMATIKA DAN PENGOLAHAN DATA ELEKTRONIK TERHADAP WARUNG INTERNET DI KOTA PEKANBARU - R. Rionaldo Putra Perdana; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Supervision of Internet cafes were conducted by the Department of Transportation, Communication and Information Pekanbaru is a reference of Regional Regulation Pekanbaru No. 7 of 2000, on license business premises and supervision of internet cafes which regulate Internet cafes that violates the kententuan formulated by the government by the Department of Transportation Communication and Information Pekanbaru. But the fact of internet cafes in the city of Pekanbaru are still many who violate the provisions that have been set because there are many internet cafes that use barriers are high, yet block sites pornography, and gambling, and many were found internet cafes which does not have a business license. Study of the phenomenon, the problem in this research is how the supervision of internet cafes in the city of Pekanbaru and the factors that influence the supervision of internet cafes in the city of Pekanbaru. This study refers to the theoretical concept Sukanto, where effective monitoring contains elements for standard or measure, an assessment of the work or conduct assessments and corrective action against the irregularities that occurred. This research is a descriptive study, in which the author presents and describes how surveillance of internet cafes in the city of Pekanbaru, especially in Sub Tampan. And to know the factors that affect the supervision of the internet cafes. The technique of collecting data is to interview and that menjdi key informant is a team supervision, cafe owners and community leaders. Results of the study found that pngawasan shop intenet in Pekanbaru especially in District Charming in the state is not good because there are still many warumg internet which has a barrier that is not in accordance with, and still finding internet cafes are not blocked situ-site pornography and gambling, and there are still many internet cafes that do not have a place of business license. The factors that affect the supervision of internet cafes in the city of Pekanbaru, especially in Sub Tampan are factors of human resources is still low level of education officer oversight and insufficient number of officers monitoring the field whose job is to monitor and record violations internet cafes, actor funds which is still a lack of cost to socialize. Keywords: Monitoring, standards, assessment